(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mergers as well as acquisitions are increasing their worth and have been a strategic option for companies that is usually applicable. The aim of received fresh information from the acquired company and then transferred this data along with other fields in the acquiring firm is typically a major cause behind an acquisition. Furthermore, for the transfer of information in every SA, the tacit and explicit nature of expertise is essential. In fact, the process of transfer of knowledge is complicated and dynamic and thus numerous challenges may arise in the process. The transfer of expertise in procurement and fusion may be a problem, but it would be necessary and vital when used in beneficial fashion for businesses.